Georeferenced data with mobile telephones for psychosocial therapies - Ferrás Sexto, Carlos; García, Yolanda (MEDICA REVIEW. International Medical Humanities Review / Revista Internacional de Humanidades Médicas, 2019)
The mobile phone is rapidly disseminated around the world and can become an instrument of universal communication between people. It is of great value for mental health therapies since it can capture and offer objective data for the psychological and social evaluation of the patient. They can provide geo-referenced data for spatial analysis and cartography of the context, the social and cultural environment of the places of people's daily life, and with them it is possible to prepare maps of mental health, emotions, suffering, depression and anxiety that can contribute to the biopsychosocial diagnosis of the patient. There are great possibilities to apply the results of interdisciplinary research among geographers, psychologists and social workers in psychosocial therapies. In these pages we present the results of a systematic review of the most important scientific production identified in the academic databases based on search and selection criteria established in advance. We reflect on the contributions of spatial analysis and mobile phones for psychosocial therapies and try to define the guidelines and questions that future research should formulate.